Rajiv Gandhi directed Indian foreign policy from 1984 to 1989 - , Rese. Nour Khader Ali; Ibtisam Salman Saeed (Journal of College of Education, 2024)
Rajiv Gandhi, as one of the major foreign policy makers made significant contributions in the field of India's foreign policy, The main plank of Rajiv's foreign policy was to maintain good and friendly relations with all countries of the world including India's immediate neighbours, It is noteworthy that apart from directing Foreign policy, Rajiv also played a crucial role in resolving several international issues thus promoting friendly relations not only with India's immediate neighbors but also with the then major powers.
Keywords: India, Pakistan, Rajiv Gandhi, foreign policy, South Asia